LEVANTAMENTO BIBLIOGRÁFICO DO USO DA MACONHA: DADOS QUÍMICOS E FARMACOLÓGICOS - Martinazo, Emanuela G.; Saturno, Camila; Hochmüller, Laura H. L.; Lopes, Tatiana B. (Salão do Conhecimento, 2013)
Resumo